Public policy, bureaucracy and prejudices: evidence of prevalence of biased attitudes among bureaucrats. (2016) - Goel, Sangeeta
This study gives evidence of biased attitudes of bureaucracy deployed in public sector. 229 bureaucrats of varied seniority and decision making levels were deployed and using a standardised inventory, and the hypotheses were tested. Results showed that both male and female bureaucrats across the country harboured strong bias, irrespective of age, seniority and decision levels. The 'sex' of the bureaucrats was a significant predictor of differences. Study has policy implications since bureaucrats, by virtue of authority and power, they exercise, need to be impartial. The results suggest that bureaucrats despite education, sensitisation and public policies, fail to rise above their own cognitive biases, which might be, adversely impacting the functioning of public sector. Using cognitive perspective and a theoretical framework drawn from psychology, to study, a key factor which precedes agency's behaviour, have been rare in policy sciences. Besides the use of real participants, the study also uncovers the dark side of bureaucracy.